Lung Transplantation and the Era of the Sensitized Patient - Young, Katherine A.; Ali, Hakim A.; Beermann, Kristi J.; Reynolds, John M.; Snyder, Laurie D. (Frontiers in Immunology, 2021)
Long term outcomes in lung transplant are limited by the development of chronic lung allograft dysfunction (CLAD). Within the past several decades, antibody-mediated rejection (AMR) has been recognized as a risk factor for CLAD. The presence of HLA antibodies in lung transplant candidates, “sensitized patients” may predispose patients to AMR, CLAD, and higher mortality after transplant. This review will discuss issues surrounding the sensitized patient, including mechanisms of sensitization, implications within lung transplant, and management strategies.